Review of Siyasah Tanfidziyah on the Voting Rights of Non-Domiciled Students in the 2024 Simultaneous Elections in the City of Bandung - Treissa Puspitasari; Lutfi Fahrul Rizal; Taufiq Alamsyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study discusses the implementation of voting rights for non-domiciled university students in the 2024 Simultaneous Elections in Bandung City. The research aims to examine the mechanisms and obstacles in the protection of political rights for non-domiciled students by the General Elections Commission (KPU) during the 2024 elections, based on Law Number 7 of 2017 concerning General Elections. In addition, the siyasah tanfidziyah perspective in this study highlights the government’s responsibility to ensure accessible political rights for student groups with high mobility. This research was conducted using a qualitative method with a juridical-empirical approach. The findings indicate that although technical regulations such as the mechanism for moving voting locations are available, administrative, socialization, and technical barriers still hinder the optimal participation of non-domiciled students. Government policies should reflect the principles of siyasah tanfidziyah, such as justice, trustworthiness, and responsibility, in guaranteeing the voting rights of all citizens.